Urban Heat Island phenomenon in Colombo: An analysis of its causes, impacts, and mitigation strategies - Sumaiya, M.S.P.; Ruzaik, Fareena; Hasmath, M.J.J. (University of Colombo, 2025)
Global warming is a significant environmental problem that currently affects a wide variety of organisms. The Urban Heat Island (UHI) phenomenon, in which urban areas have hotter temperatures than nearby rural or suburban areas, is caused by urbanization. However, global warming amplifies the effects of UHI, which in turn may intensify global warming trends. Weather patterns, species behaviors and habitats, water resources, and air quality are all significantly impacted by this temperature increase. As a result, many nations experience negative effects on their social, economic, health, and environmental conditions. This article focuses on Colombo, a rapidly developing city in Sri Lanka, as a case study to investigate the causes, impacts, and mitigation methods of urban heat islands. The study primarily utilizes secondary data collection methods, drawing information from research articles, journals, publications, annual reports, relevant books, and credible online sources. The secondary data were analyzed qualitatively and presented descriptively. The research findings reveal the pronounced urban heat island effects in Colombo. the city’s Urban Heat Islands (UHIs) have a number of negative effects, such as elevated emissions of air pollutants, weakened human health, changed weather patterns, and worsened water quality. The loss of natural landscapes, the thermal properties of urban materials like concrete and asphalt, heat retaining urban geometry, and increased human activity are some of the contributing factors to these effects. Greenhouse gas emissions and population growth contribute to UHI as well as to climate change. Furthermore, topography may influence the distribution of local temperature distribution. The study suggests several measures to lessen these issues in Colombo, such as creating sustainable urban infrastructure, increasing the number of trees and other vegetation, installing green roofs or reflective cool roofs, putting cool pavements in place, adapting smart growth principles, and encouraging effective transportation systems.
Keywords: Urban Heat Islands; Global warming; Air quality; Health; Population; Geometry; Weather; Transport